Chronic heat stress and feed restriction affects carcass composition and the expression of genes involved in the control of fat deposition in broilers - De Antonio, J. [UNESP]; Fernandez-Alarcon, M. F. [UNESP]; Lunedo, R. [UNESP]; Squassoni, G. H. [UNESP]; Ferraz, A. L.J.; Macari, M. [UNESP]; Furlan, R. L. [UNESP]; Furlan, L. R. (Cambridge University Press (CUP), 2017)
Heat stress (HS) is among the major limiting factors to growth of broilers. Heat stress also results in changes in the characteristics of the carcass, such as an increase in fat deposition. The molecular mechanisms responsible for fat deposition in broilers as a response to HS remain unknown. The current study aimed to describe the molecular mechanisms associated with the effects of high temperature and feed restriction due to chronic heat exposure at 32 °C, and to describe the resulting changes in the growth performance and carcass characteristics of the broilers at 21 and 42 days of age. In the current study, 441 male Cobb-500® broilers were subjected to three treatments that differed in rearing temperature and feeding regime: chronic HS fed ad libitum (HS/AL), thermoneutral environment fed ad libitum (TN/AL) and TN and pair-feeding on the feed intake (FI) of the heat-exposed group (TN/PF). HS increased fat content in the breast and wings and decreased fat content in the legs, but did not influence abdominal fat. These effects occurred regardless of reducing consumption induced by HS. Furthermore, HS, independently of reduced FI, increased liver sterol-regulatory element-binding protein-1 (SREBP-1) mRNA in both ages and growth hormone receptor (GHR) mRNA at 42days, whereas feed restriction reduced GHR mRNA only at 21days. In conclusion, increased fat content in the breast and wings was accompanied by a higher gene expression of GHR and SREBP-1, suggesting the involvement of both genes in the control of fat deposition in broilers exposed to HS.